2022
DOI: 10.1002/sd.2473
|View full text |Cite
|
Sign up to set email alerts
|

Environmental sustainability in South Africa: Understanding the criticality of economic policy uncertainty, fiscal decentralization, and green innovation

Abstract: South Africa, like most developing nations, is confronted with choosing between the need to advance their economy and the need to protect the environment. The United Nations Sustainable Development Goals 11, 12 & 13) provide a strong foundation for this investigation. To this end, the current research investigates the combined impacts of economic policy uncertainty, fiscal decentralization, and green innovation on environmental sustainability for the instance of South Africa with yearly frequency data from 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 49 publications
(16 citation statements)
references
References 90 publications
0
16
0
Order By: Relevance
“…Isik et al (2020) validated this evidence in their analysis of G7 nations from 1995 to 2015 for France, but EKC was not valid in the US, the UK, Japan, Italy, Germany, and Canada. Additionally, according to Udeagha and Muchapondwa (2022b), EKC was found in South Africa from 1960 to 2020. Our evidence further supports those of Murshed (2021) for six South Asian economies.…”
Section: Dynamic Ardl Simulation Model Resultsmentioning
confidence: 99%
“…Isik et al (2020) validated this evidence in their analysis of G7 nations from 1995 to 2015 for France, but EKC was not valid in the US, the UK, Japan, Italy, Germany, and Canada. Additionally, according to Udeagha and Muchapondwa (2022b), EKC was found in South Africa from 1960 to 2020. Our evidence further supports those of Murshed (2021) for six South Asian economies.…”
Section: Dynamic Ardl Simulation Model Resultsmentioning
confidence: 99%
“…Additionally, their actual R&D investment rose by 3.8%. In a similar vein, public R&D spending was 1.3%, whereas private R&D spending was over 28% (Udeagha & Muchapondwa, 2022a, 2022b). Therefore, this study is crucial for the BRICS nations under examination.…”
Section: Introductionmentioning
confidence: 90%
“…EPS shows the potential and successes in the implementation of environmental rules, and explains how economies are motivated by ecological goals in relation to the average standards of nations when implementing such regulations (Udeagha & Muchapondwa, 2022b). Kongbuamai et al (2021) demonstrated that EPS plays a major role in accomplishing sustainable development goals (SDGs) while preserving ecological quality.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The most notable finding of the researchers is the distinction between the short and long-term effects of WUI on CO 2 emissions, as economic uncertainty reduces carbon emissions in the short run, allowing for climate improvement. However, in the long run, the influence positively affects CO 2 emissions (Udeagha, M. C. and Muchapondwa, 2022), where economic uncertainty is regarded as a cause of environmental degradation in the study sample. Syed et al (2022) studied the impact of EPU and geopolitical risks (GPR) on CO 2 emissions in BRICST countries from 1990 to 2015.…”
Section: Literature Reviewmentioning
confidence: 97%